What Is a Singularity in Geometrized Newtonian Gravitation?. Issue 5 (December 2014) - Weatherall, James Owen
Abstract : I discuss singular space-times in the context of the geometrized formulation of Newtonian gravitation. I argue first that geodesic incompleteness is a natural criterion for when a model of geometrized Newtonian gravitation is singular, and then I show that singularities in this sense arise naturally in classical physics by stating and proving a classical version of the Raychaudhuri-Komar singularity theorem.